2020
DOI: 10.1097/psy.0000000000000862
|View full text |Cite
|
Sign up to set email alerts
|

Open- and Closed-Label Placebo and Nocebo Suggestions About a Sham Transdermal Patch

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 62 publications
0
10
1
Order By: Relevance
“…Contrary to our second hypothesis, the positive and negative suggestions about contagious itch failed to modulate participants' itch expectancies as well as their general itch experience. These findings are somewhat unexpected in light of previous work that shows that verbal suggestions can modulate expectancies about, and the experience of, cutaneous itch e.g., 12,33,34 On the contrary, in previous research catastrophizing information only influenced scratching responses and did not affect contagious itch. 20 These effects were moreover only found in patients with dermatological conditions, but not in healthy controls.…”
Section: Discussioncontrasting
confidence: 85%
“…Contrary to our second hypothesis, the positive and negative suggestions about contagious itch failed to modulate participants' itch expectancies as well as their general itch experience. These findings are somewhat unexpected in light of previous work that shows that verbal suggestions can modulate expectancies about, and the experience of, cutaneous itch e.g., 12,33,34 On the contrary, in previous research catastrophizing information only influenced scratching responses and did not affect contagious itch. 20 These effects were moreover only found in patients with dermatological conditions, but not in healthy controls.…”
Section: Discussioncontrasting
confidence: 85%
“…Mediation analysis demonstrated that positive VSs reduced expected itch compared to negative VSs (path a 1 : b X→M = -1.84, SE = 0.31, p < 0.001; findings of the separate studies are described in Meeuwis et al, 2019;Meeuwis et al, 2021). However, 3).…”
Section: Closed-label Positive Versus Negative Verbal Suggestions (Studies 2 and 3)mentioning
confidence: 88%
“…Mediation analysis demonstrated that positive VSs reduced expected itch compared to negative VSs (path a 1 : b X→M = -1.72, SE = 0.30, p < 0.001; findings of the separate studies are described in Meeuwis et al, 2019;Meeuwis et al, 2021). Lower post-VSs expected itch in turn was associated with lower post-VSs mean itch (path b 1 : b M→Y = 0.17, SE = 0.08, p = 0.032).…”
Section: Open-label Positive Versus Negative Verbal Suggestions (Studies 2 and 3)mentioning
confidence: 91%
See 2 more Smart Citations